2017
DOI: 10.18203/2349-3291.ijcp20164034
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlation of soil transmitted helminth infection to the degree of anemia and nutritional status among pediatric patients of age group 6-14 years in Kishanganj, Bihar, India

Abstract: Soil-transmitted helminths (STHs) are among the most common chronic infections worldwide mainly in low and middle income countries. 1 Helminthic infestations are infamous among children in rural areas such as aborigine settlements associated with substandard sanitation system and low socioeconomic status. Among young, in tropical and subtropical regions in particular, these constitute a major health problem. The three common STH species ABSTRACT Background: Intestinal parasites are a major public health proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
4
3
0
Order By: Relevance
“…In the present study, Trichuris trichura had more infection in male (13.95%) than female (10.31% ). Similar result was also observed by Ahmed et al (2013) and Kumar et al (2017).…”
Section: Resultssupporting
confidence: 91%
“…In the present study, Trichuris trichura had more infection in male (13.95%) than female (10.31% ). Similar result was also observed by Ahmed et al (2013) and Kumar et al (2017).…”
Section: Resultssupporting
confidence: 91%
“…T. trichiura (20.75%) was also moderately prevalent; topmost (16.95%) in male (Table 1). Similar result was found by Uddin and Khanum (2008) and Kumar et al (2017). In the present study, A. lumbricoides was the most prevalent (42.11%) among the children aged 10-12 years old (Table 2).…”
Section: Resultssupporting
confidence: 88%
“…Children of illiterate mothers (unable to read and write) were more prone to helminth infestation (91.89%) (Table 3) which is supported by another study conducted among the Mexican children; revealed low maternal education level was highly associated with parasitic infection (p < 0.001) (Quihui et al 2006). Kumar et al (2017) found that children with low educational status were more likely to have intestinal parasites too.…”
Section: Resultssupporting
confidence: 54%
“…Similar findings were reported in Dhaka, Bangladesh by Banu S. S. et al [ 7 ] and in Nigeria by Saka MI et al [ 8 ] The present study found out that the age and caste wise association with helminthes was statistically significant (p value = 0.005). Kumar S et al in Bihar[ 9 ] reported similar observations. Nearly half of the subjects belonged to lower middle class IV (48.7%) followed by middle class III who account for 28%; however, the association between helminthic infection and the socioeconomic status of participants was found to be statistically significant (p value = 0.010).…”
Section: Discussionsupporting
confidence: 56%
“…Nearly half of the subjects belonged to lower middle class IV (48.7%) followed by middle class III who account for 28%; however, the association between helminthic infection and the socioeconomic status of participants was found to be statistically significant (p value = 0.010). Banu SS et al , Dhaka, Bangladesh[ 7 ] and Kumar S et al [ 9 ] also found a similar significant association of socioeconomic status and Helminthic infestation. Kaur H and Sween[ 10 ] also found higher incidence of parasitic infections among children belonging to low socioeconomic status.…”
Section: Discussionmentioning
confidence: 74%